TINDAK UJAR ILOKUSI DALAM FILM GIFTED HANDS KARYA JOHN PIELMEIER SUATU ANALISIS PRAGMATIK - KARANGAN, TORMY VALEN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research is entitled ?Illocutionary Act in the Film Gifted Hands by John Pielmeier: A Pragmatic Analysis?. It is an analysis of pragmatic investigation that focuses on one aspect of speech act called illocutionary act. It is an attemp to find the kinds and functions of illocutionary act in the film. The data has been taken from the characters utterances in the film. The writer analyzed the data descriptively by concentrating on utterances which contain illocution. The theory used in this research is taken from Searle?s theory about illocutionary acts classification. The finding of this research shows the kinds and functions of the illocutionary act that are found in the film Gifted Hands. These are classified into five categories, those are assertives: stating, suggesting, vowing, and reporting; directives: ordering, commending, requesting, and advising; commissives: promising and offering; expressive: thanking, praising, and blaming; declaratives: naming, suspending, and declaring. Theoretically, the writer extends that this research can give some contribution for students to understand kinds of illocutionary act and their functions which are not only in this film, but also in other literary works especially in daily communication. Keywords : Illocutionary, Speech Act, Film Gifted Hands, Pragmatic Analysis